Electrolyte, secondary battery, and electric device
By using new lithium salts containing alkyl ethers, sulfonic acid amines and fluorine elements in the electrolyte, the problems of low lithium ion migration and unstable SEI interface layer in traditional lithium ion batteries are solved, and the fast charging and cycling performance of the battery is significantly improved.
Patent Information
- Application Number
- CN202411768541.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-03
- Publication Date
- 2025-03-14
AI Technical Summary
The number of lithium ion migrations in traditional lithium-ion batteries is low and cannot form a stable SEI interface layer, which limits its fast charging and cycling performance.
A new electrolyte is adopted, containing lithium salts containing C3-C20 alkyl ether, sulfonic acid amine group and fluorine element in the molecular structure, and lithium ions are captured through the ether group part. The sulfonic acid amine anion promotes the formation of SEI film, and the fluorine element stabilizes the interface film.
It significantly improves the number of lithium ion migrations, improves the battery's fast charging capability and cycling performance, inhibits the increase in battery internal resistance and volume expansion, and reduces irreversible losses.
Smart Images

Figure BDA0005169991570000011 
Figure BDA0005169991570000021 
Figure BDA0005169991570000022
Abstract
Description
Technical Field
[0001] The present application relates to the field of battery technology, and in particular to an electrolyte, a secondary battery and an electrical device. Background Art
[0002] The rapid development of the global economy has caused the depletion of traditional petrochemical energy and environmental pollution, which have become increasingly prominent. As electric vehicles enter thousands of households, higher requirements are placed on power batteries. Fast charging has become an important factor affecting the application of electric vehicles.
[0003] Traditional lithium salts have a low lithium ion migration number and cannot form a stable SEI interface layer, which is one of the important factors affecting their ability to achieve higher-rate fast charging and longer cycles.
[0004] In view of this, this application is filed. Summary of the invention
[0005] The purpose of the present application is to overcome the deficiencies of the prior art and provide an electrolyte, a secondary battery and an electrical device, wherein the electrolyte can significantly improve the fast charging performance and cycle performance of the secondary battery.
[0006] To achieve the above-mentioned object, the first aspect of the present application provides an electrolyte, comprising a lithium salt, wherein the lithium salt comprises at least one of the compound represented by Formula I and the compound represented by Formula II:
[0007]
[0008] In Formula I, R1 comprises at least one of C1-C6 alkylene and C1-C6 alkylene ether; R2 comprises C3-C 20 Alkyl ethers;
[0009] In formula II, R3 comprises at least one of C1-C6 alkylene and C1-C6 alkylene ether; R4 comprises C3-C 20 Alkyl ether.
[0010] As an embodiment of the present application, R1 includes at least one of C1-C2 alkylene and C1-C2 alkylene ether; R2 includes C3-C6 alkyl ether; and / or
[0011] The R3 includes at least one of C1-C2 alkylene and C1-C2 alkylene ether; and R4 includes C3-C6 alkyl ether.
[0012] As an implementation scheme of the present application, at least one of the following (a) to (b) is satisfied:
[0013] (a) The compound represented by formula I comprises at least one of the following compounds:
[0014]
[0015] (b) The compound represented by formula II comprises at least one of the following compounds:
[0016]
[0017] As an embodiment of the present application, the mass percentage of the lithium salt in the electrolyte is 8-20%.
[0018] As an embodiment of the present application, the electrolyte further includes a first additive, and the first additive includes at least one of a sulfur-containing additive and a boron-containing additive; the mass percentage of the first additive in the electrolyte is 0.1 to 6%.
[0019] As an embodiment of the present application, the sulfur-containing additive includes at least one of 1,3-propane sultone, vinyl sulfate, and methylene disulfonate; and / or
[0020] The boron-containing additive includes at least one of lithium difluorooxalatoborate (LiODFB), lithium bis(oxalatoborate) (LiBOB), and lithium tetrafluoroborate (LiBF4).
[0021] As an embodiment of the present application, the first additive includes a sulfur-containing additive and a boron-containing additive, the mass percentage of the sulfur-containing additive in the electrolyte is 0.1-3%; the mass percentage of the boron-containing additive in the electrolyte is 0.1-3%.
[0022] As an embodiment of the present application, in the electrolyte, the mass ratio of the lithium salt to the first additive is (5-14):1.
[0023] A second aspect of the present application provides a secondary battery, comprising the above-mentioned electrolyte.
[0024] A third aspect of the present application provides an electrical device, comprising the secondary battery described above, wherein the secondary battery serves as a power supply for the electrical device.
[0025] The beneficial effect of the present application is that the lithium salt described in the present application has a molecular structure containing C3-C 20 Alkyl ether, sulfonamide group and fluorine element have large dipole moment and high donor number. The ether group can effectively capture lithium ions, significantly increase the lithium ion migration number and improve the fast charging capability. The sulfonamide anion has a high donor number (DN value), which can decompose at the positive electrode to produce LiF, Li3N and Li2S x O yThe CEI interface layer can inhibit the phase change of the positive electrode interface and the dissolution of excessive metals, promote the formation of a dense SEI film rich in inorganic layers, inhibit the increase of battery internal resistance and volume expansion, and reduce irreversible losses; the fluorine element can promote the formation of a more stable interface film, which is beneficial to inhibit the side reaction of the electrolyte, thereby avoiding the side reaction products from blocking the ion migration channel and causing ion aggregation; at the same time, the lithium salt can react with Li + Combined with other materials, they participate in the formation of a solvation structure, inhibit solvent decomposition, and significantly improve the cycle performance of secondary batteries. DETAILED DESCRIPTION
[0026] In order to make the purpose, technical scheme and advantages of the embodiments of the present application clearer, the technical scheme in the embodiments of the present application will be described clearly and completely below. Obviously, the described embodiment is a step-by-step embodiment of the present application, rather than a full-step embodiment. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present application.
[0027] In the present application, the technical features described in an open manner include closed technical solutions composed of the listed features, and also include open technical solutions containing the listed features.
[0028] In this application, when it comes to numerical ranges, unless otherwise specified, the above numerical ranges are deemed to be continuous and include the minimum and maximum values of the range, as well as each value between such minimum and maximum values. Further, when a range refers to an integer, each integer between the minimum and maximum values of the range is included. In addition, when multiple ranges are provided to describe features or characteristics, the ranges can be merged. In other words, unless otherwise specified, all ranges disclosed herein should be understood to include any and all subranges included therein.
[0029] The present application provides an electrolyte solution including a lithium salt, wherein the lithium salt includes at least one of the compound shown in Formula I and the compound shown in Formula II:
[0030]
[0031] In Formula I, R1 comprises at least one of C1-C6 alkylene and C1-C6 alkylene ether; R2 comprises C3-C 20 Alkyl ethers;
[0032] In formula II, R3 comprises at least one of C1-C6 alkylene and C1-C6 alkylene ether; R4 comprises C3-C 20 Alkyl ether.
[0033] Among them, the lithium salt described in this application contains C3-C 20Alkyl ether, sulfonamide group and fluorine element have large dipole moment and high donor number. The ether group can effectively capture lithium ions, significantly increase the lithium ion migration number and improve the fast charging capability. The sulfonamide anion has a high donor number (DN value), which can decompose at the positive electrode to produce LiF, Li3N and Li2S x O y The CEI interface layer can inhibit the phase change of the positive electrode interface and the dissolution of the transition metal, promote the formation of a dense SEI film rich in inorganic layers, inhibit the increase of the internal resistance and volume expansion of the battery, and reduce irreversible losses; the fluorine element can promote the formation of a more stable interface film, which is beneficial to inhibit the side reaction of the electrolyte, thereby avoiding the side reaction products blocking the ion migration channel and causing ion aggregation; at the same time, the lithium salt can react with Li + Combined with other materials, they participate in the formation of a solvation structure, inhibit solvent decomposition, and significantly improve the cycle performance of secondary batteries.
[0034] In the above formula I and formula II, the substituents are as follows:
[0035] The alkylene group in the C1-C6 alkylene group (alkylene group having 1 to 6 carbon atoms) refers to a free radical of a saturated or unsaturated aliphatic group, including a branched alkyl group and a cyclic alkyl group.
[0036] Exemplarily, the C1-C6 alkylene group includes a C1-C6 saturated alkyl group, and more preferably, a straight chain alkyl group having 1 to 4 carbon atoms, a branched chain alkyl group having 2 to 4 carbon atoms, and a cyclic alkyl group having 2 to 4 carbon atoms. Examples of the alkyl group include: methyl, ethyl, n-propyl, isopropyl, n-butyl, isobutyl, sec-butyl, tert-butyl, n-pentyl, isopentyl, neopentyl, cyclopentyl, and cyclohexyl;
[0037] C3~C 20 The alkyl group in the alkyl ether (alkyl ether having 3 to 20 carbon atoms) refers to a free radical of a saturated or unsaturated aliphatic group, including straight-chain alkyl ether, branched-chain alkyl ether, and cycloalkyl ether.
[0038] For example, C3~C 20 Alkyl ethers include C3~C 20 Saturated alkyl ether, C3~C 20 Alkenyl ether and C3~C 20 Alkynyl ethers are preferably linear alkyl ethers having 3 to 10 carbon atoms, branched alkyl ethers having 3 to 10 carbon atoms, or cyclic alkyl ethers having 3 to 10 carbon atoms. 20Examples of alkyl ethers include: methyl ether, ethyl ether, n-butyl ether, n-propyl ether, n-pentyl ether, dioxolane, diethylene glycol dimethyl ether, tetrahydrofuran, 1,4-dioxane, ethylene oxide, 1,2-propylene oxide, 1,2-butylene oxide, isopropyl ether, n-butyl ether, sec-butyl ether, isobutyl ether, n-pentyl ether, isopentyl ether, neopentyl ether, 18-crown-6, 15-crown-5, dicyclohexane-18-crown-6, and 12-crown-4.
[0039] In one embodiment, R1 comprises at least one of C1-C2 alkylene and C1-C2 alkylene ether; R2 comprises C3-C6 alkyl ether; and / or
[0040] The R3 includes at least one of C1-C2 alkylene and C1-C2 alkylene ether; and R4 includes C3-C6 alkyl ether.
[0041] In one embodiment, at least one of the following (a) to (b) is satisfied:
[0042] (a) The compound represented by formula I comprises at least one of the following compounds:
[0043]
[0044] (b) The compound represented by formula II comprises at least one of the following compounds:
[0045]
[0046] In particular, when the compound represented by formula I and the compound represented by formula II are at least one of the above compounds, the ether group part in its molecular structure can effectively capture lithium ions, significantly increase the number of lithium ion migration, and thus improve the fast charging performance of the secondary battery.
[0047] The synthetic routes of the compound represented by the above formula I and the compound represented by the above formula II (hereinafter referred to as lithium salt A1, lithium salt A2, lithium salt A3, lithium salt A4, lithium salt B1, lithium salt B2, lithium salt B3, lithium salt B4, respectively) are as follows:
[0048]
[0049]
[0050] More specifically, the preparation methods and characterizations of the above-mentioned lithium salts A1-A4 and lithium salts B1-B4 are as follows:
[0051] The preparation method of lithium salt A1 comprises the following steps: slowly dropping trifluoromethanesulfonic anhydride (1.01 equivalents, Y1) into a mixed solution of 2-(2-(2-methoxyethoxy)ethoxy)ethylamine (1 equivalent, Z1) and triethylamine (1.3 equivalents) in acetonitrile (50 ml) at -80°C, stirring for 2 hours after the dropwise addition is completed, removing the solvent under reduced pressure after the reaction is completed, dissolving the residue with a concentrated sodium hydroxide solution, extracting the byproduct with dichloromethane, neutralizing with hydrochloric acid, and extracting with dichloromethane again to obtain product Z2;
[0052] The above product Z2 was dissolved in 30 ml of anhydrous acetonitrile solvent, and then lithium hydride (1.01 equivalent) was slowly added in an ice-water bath. After the addition was complete, the temperature was raised to room temperature and stirring was continued for 6 hours. After the reaction was completed, the solvent was removed under reduced pressure and then recrystallized in ether to obtain lithium salt A1; the yield of the two-step reaction was 56.1%. The structural confirmation data of lithium salt A1: 1 H NMR (DMSO, 300MHZ) δ (ppm): 1.5 (m, 2H), 3.4 (m, 5H), 3.52 (m, 6H), 3.55 (m, 2H). 13 CNMR(CDCl3,100MHZ)δ(ppm):151,71.6,70.4,70.1,59.3,59,13.
[0053] The preparation method of lithium salt A2 comprises the following steps: slowly dropping trifluoromethanesulfonic anhydride (1.01 equivalents, Y1) into a mixed solution of 1,4-dioxane-2-methylamine (1 equivalent, Z3) and triethylamine (1.3 equivalents) in acetonitrile (50 ml) at -80°C, stirring for 2 hours after the dropwise addition is completed, removing the solvent under reduced pressure after the reaction is completed, dissolving the residue with a concentrated sodium hydroxide solution, extracting the byproduct with dichloromethane, neutralizing with hydrochloric acid, and extracting with dichloromethane again to obtain product Z4;
[0054] The above product Z4 was dissolved in 30 ml of anhydrous acetonitrile solvent, and then lithium hydride (1.01 equivalent) was slowly added in an ice-water bath. After the addition was complete, the temperature was raised to room temperature and stirring was continued for 6 hours. After the reaction was completed, the solvent was removed under reduced pressure, and then recrystallized in ether to obtain lithium salt A2; the yield of the two-step reaction was 55.8%. The structural confirmation data of lithium salt A2: 1 H NMR(DMSO,300MHZ)δ(ppm):1.3-1.6(m,2H),3.5-3.72(m,7H), 13 CNMR(CDCl3,100MHZ)δ(ppm):151,79.2,71,67.5,60.5,14.
[0055] The preparation method of lithium salt A3 comprises the following steps: slowly dropping trifluoromethanesulfonic anhydride (1.01 equivalents, Y1) into a mixed solution of 2-(aminomethyl)-1,3-dioxolane (1 equivalent, Z5) and triethylamine (1.3 equivalents) in acetonitrile (50 ml) at -80°C, stirring for 2 hours after the dropwise addition is completed, removing the solvent under reduced pressure after the reaction is completed, dissolving the residue with a concentrated sodium hydroxide solution, extracting the byproduct with dichloromethane, neutralizing with hydrochloric acid, and extracting with dichloromethane again to obtain product Z6;
[0056] The above product Z6 was dissolved in 30 ml of anhydrous acetonitrile solvent, and then lithium hydride (1.01 equivalent) was slowly added in an ice-water bath. After the addition was complete, the temperature was raised to room temperature and stirring was continued for 6 hours. After the reaction was completed, the solvent was removed under reduced pressure and then recrystallized in ether to obtain lithium salt A3; the yield of the two-step reaction was 54.6%. The structural confirmation data of lithium salt A3: 1 H NMR(DMSO,300MHZ)δ(ppm):1.6(m,2H),3.87(m,2H),4.0(m,2H),5.56(m,1H), 13 CNMR(CDCl3,100MHZ)δ(ppm):151,104,64.4,18.
[0057] The preparation method of lithium salt A4 comprises the following steps: slowly dropping trifluoromethanesulfonic anhydride (1.01 equivalents, Y1) into a mixed solution of 2,2-dimethyl-1,3-dioxolane-4-methylamine (1 equivalent, Z7) and triethylamine (1.3 equivalents) in acetonitrile (50 ml) at -80°C, stirring for 2 hours after the dropwise addition is completed, removing the solvent under reduced pressure after the reaction is completed, dissolving the residue with a concentrated sodium hydroxide solution, extracting the byproduct with dichloromethane, neutralizing with hydrochloric acid, and extracting with dichloromethane again to obtain product Z8;
[0058] The above product Z8 was dissolved in 30 ml of anhydrous acetonitrile solvent, and then lithium hydride (1.01 equivalent) was slowly added in an ice-water bath. After the addition was complete, the temperature was raised to room temperature and stirring was continued for 6 hours. After the reaction was completed, the solvent was removed under reduced pressure and then recrystallized in ether to obtain lithium salt A4; the yield of the two-step reaction was 53.6%. The structural confirmation data of lithium salt A4: 1 H NMR (DMSO, 300MHZ) δ (ppm): 1.2 (m, 6H), 1.6 (m, 2H), 3.6-3.9 (m, 3H), 13 CNMR(CDCl3,100MHZ)δ(ppm):151,118.9,73.4,72,26.2,14.
[0059] The preparation method of lithium salt B1 comprises the following steps: slowly dropping 2-hydroxyethanesulfonyl chloride (1.01 equivalent, Y2) into a mixed solution of 1-(2-chloroethoxy)-2-methoxyethane (Z9, 1 equivalent) and potassium carbonate (1.3 equivalent) in acetonitrile (50 ml) under an ice-water bath, heating to room temperature after the dropwise addition is completed, stirring is continued for 6 hours, and after the reaction is completed, the solvent is removed under reduced pressure to obtain a crude product Z11;
[0060] The product Z11 was dissolved in 30 ml of acetonitrile solvent, potassium carbonate was added, and then the mixed solution of trifluoromethanesulfonyl chloride was slowly added dropwise in an ice-water bath. After the addition was completed, the temperature was raised to room temperature and stirring was continued for 6 hours. After the reaction was completed, the solvent was removed under reduced pressure, and the residue was dissolved with a concentrated sodium hydroxide solution. The by-product was extracted with dichloromethane, neutralized with hydrochloric acid, and extracted again with dichloromethane to obtain the product Z12;
[0061] The above product Z12 was dissolved in 30 ml of anhydrous acetonitrile solvent, and then LiBF4 (1.01 equivalent) was slowly added in an ice-water bath. After the addition was complete, the temperature was raised to room temperature and stirring was continued for 6 hours. After the reaction was completed, the solvent was removed under reduced pressure and then recrystallized in ether to obtain lithium salt B1; the yield of the three-step reaction was 45.1%. The structural confirmation data of lithium salt B1: 1 H NMR (DMSO, 300MHZ) δ (ppm): 3.40 (m, 3H), 3.52 (m, 6H), 3.55 (m, 2H), 3.58 (m, 2H), 3.93 (m, 2H). 13 CNMR(CDCl3,100MHZ)δ(ppm):149,71.6,70.4,70.1,64,59.3,49.
[0062] The preparation method of lithium salt B2 comprises the following steps: slowly dropping 2-hydroxyethanesulfonyl chloride (1.01 equivalent, Y2) into a mixed solution of 2-chloromethyl-1,4-dioxane (Z13, 1 equivalent) and potassium carbonate (1.3 equivalent) in acetonitrile (50 ml) under an ice-water bath, heating to room temperature after the dropwise addition is completed, stirring is continued for 6 hours, and after the reaction is completed, the solvent is removed under reduced pressure to obtain a crude product Z14;
[0063] The product Z14 was dissolved in 30 ml of acetonitrile solvent, potassium carbonate was added, and then the mixed solution of trifluoromethanesulfonyl chloride was slowly added dropwise in an ice-water bath. After the addition was completed, the temperature was raised to room temperature and stirring was continued for 6 hours. After the reaction was completed, the solvent was removed under reduced pressure, and the residue was dissolved with a concentrated sodium hydroxide solution. The by-product was extracted with dichloromethane, neutralized with hydrochloric acid, and extracted again with dichloromethane to obtain the product Z15;
[0064] The above product Z15 was dissolved in 30 ml of anhydrous acetonitrile solvent, and then LiBF4 (1.01 equivalent) was slowly added in an ice-water bath. After the addition was complete, the temperature was raised to room temperature and stirring was continued for 6 hours. After the reaction was completed, the solvent was removed under reduced pressure and then recrystallized in ether to obtain lithium salt B2; the yield of the three-step reaction was 44.3%. The structural confirmation data of lithium salt B2: 1 H NMR(DMSO,300MHZ)δ(ppm):3.58(m,2H),3.61-3.77(m,8H),3.91(m,1H),3.93(m,2H) 13 CNMR(CDCl3,100MHZ)δ(ppm):149,79.8,68.2,67.5,64,63.8,60.8,49.
[0065] The preparation method of lithium salt B3 comprises the following steps: slowly dropping 2-hydroxyethanesulfonyl chloride (1.01 equivalent, Y2) into a mixed solution of 2-chloromethyl-1,3-dioxolane (Z16, 1 equivalent) and potassium carbonate (1.3 equivalent) in acetonitrile (50 ml) under an ice-water bath, heating to room temperature after the dropwise addition is completed, stirring is continued for 6 hours, and after the reaction is completed, the solvent is removed under reduced pressure to obtain a crude product Z17;
[0066] The product Z17 was dissolved in 30 ml of acetonitrile solvent, potassium carbonate was added, and then the mixed solution of trifluoromethanesulfonyl chloride was slowly added dropwise in an ice-water bath. After the addition was completed, the temperature was raised to room temperature and stirring was continued for 6 hours. After the reaction was completed, the solvent was removed under reduced pressure, and the residue was dissolved with a concentrated sodium hydroxide solution. The by-product was extracted with dichloromethane, neutralized with hydrochloric acid, and extracted again with dichloromethane to obtain the product Z18;
[0067] The above product Z18 was dissolved in 30 ml of anhydrous acetonitrile solvent, and then LiBF4 (1.01 equivalent) was slowly added in an ice-water bath. After the addition was complete, the temperature was raised to room temperature and stirring was continued for 6 hours. After the reaction was completed, the solvent was removed under reduced pressure, and then recrystallized in ether to obtain lithium salt B3; the yield of the three-step reaction was 44.3%. The structure confirmation data of lithium salt B3: 1 H NMR(DMSO,300MHZ)δ(ppm):3.58(m,2H),3.67(m,2H),3.87(m,2H),3.93(m,2H)4.0(m,2H),5.76(m,1H), 13 CNMR(CDCl3,100MHZ)δ(ppm):149,115.8,69.4,64.7,64,49.
[0068] The preparation method of lithium salt B4 comprises the following steps: slowly dropping 2-hydroxyethanesulfonyl chloride (1.01 equivalent, Y2) into a mixed solution of 4-chloromethyl-2,2-dimethyl-1,3-dioxolane (Z19, 1 equivalent) and potassium carbonate (1.3 equivalent) in acetonitrile (50 ml) under an ice-water bath, heating to room temperature after the dropwise addition is completed, stirring is continued for 6 hours, and after the reaction is completed, the solvent is removed under reduced pressure to obtain a crude product Z20;
[0069] The product Z20 was dissolved in 30 ml of acetonitrile solvent, potassium carbonate was added, and then the mixed solution of trifluoromethanesulfonyl chloride was slowly added dropwise in an ice-water bath. After the addition was completed, the temperature was raised to room temperature and stirring was continued for 6 hours. After the reaction was completed, the solvent was removed under reduced pressure, and the residue was dissolved with a concentrated sodium hydroxide solution. The by-product was extracted with dichloromethane, neutralized with hydrochloric acid, and extracted again with dichloromethane to obtain the product Z21;
[0070] The above product Z21 was dissolved in 30 ml of anhydrous acetonitrile solvent, and then LiBF4 (1.01 equivalent) was slowly added in an ice-water bath. After the addition was complete, the temperature was raised to room temperature and stirring was continued for 6 hours. After the reaction was completed, the solvent was removed under reduced pressure and then recrystallized in ether to obtain lithium salt B4; the yield of the three-step reaction was 43.2%. The structure confirmation data of lithium salt B4: 1 H NMR (DMSO, 300MHZ) δ (ppm): 1.21 (m, 6H), 3.58 (m, 2H), 3.61 (m, 2H), 3.87 (m, 2H), 3.93 (m, 2H), 4.12 (m, 1H), 13 CNMR(CDCl3,100MHZ)δ(ppm):149,119.2,76.2,67.5,64.1,64,49,26.2.
[0071] In one embodiment, the mass percentage of the lithium salt in the electrolyte is 8-20%, for example, it can be 8%, 9%, 10%, 11%, 12%, 13%, 14%, 15%, 16%, 17%, 18%, 19%, 20% or a range consisting of any two values therein. The amount of lithium salt is controlled within this range, and the electrolyte can balance conductivity and viscosity, increase the migration speed of lithium ions, and maintain the stability of the electrolyte.
[0072] In one embodiment, the electrolyte further includes a first additive, which includes at least one of a sulfur-containing additive and a boron-containing additive; the mass percentage of the first additive in the electrolyte is 0.1 to 6%, for example, it can be 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, 2%, 3%, 4%, 5%, 6% or a range consisting of any two of these values.
[0073] In one embodiment, the sulfur-containing additive includes at least one of 1,3-propane sultone, vinyl sulfate, and methylene methane disulfonate.
[0074] In one embodiment, the boron-containing additive includes at least one of lithium difluorooxalatoborate (LiODFB), lithium dioxalatoborate (LiBOB), and lithium tetrafluoroborate (LiBF4).
[0075] In one embodiment, the first additive includes a sulfur-containing additive and a boron-containing additive, and the mass percentage of the sulfur-containing additive in the electrolyte is 0.1-3%, for example, it can be 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, 2%, 3% or a range consisting of any two of them; the mass percentage of the boron-containing additive in the electrolyte is 0.1-3%, for example, it can be 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, 2%, 3% or a range consisting of any two of them.
[0076] In one embodiment, the electrolyte further includes an organic solvent, and the organic solvent includes at least one of ethylene carbonate (EC), propylene carbonate (PC), butylene carbonate (BC), fluoroethylene carbonate (FEC), dimethyl carbonate (DMC), ethyl methyl carbonate (EMC), diethyl carbonate (DEC), methyl propyl carbonate (MPC), diphenyl carbonate (DPhC), ethyl acetate (EA), propyl acetate (PA), methyl propionate (MP), ethyl propionate (EP), propyl propionate (PP), methyl butyrate (MB), ethyl butyrate (EB), γ-butyrolactone (γ-GBL), acetonitrile (AN), and cyclopentane sulfone (TMS).
[0077] In one embodiment, in the electrolyte, the mass ratio of the lithium salt to the first additive is (5-14):1, for example, it can be 5:1, 6:1, 8:1, 10:1, 12:1, 14:1 or a range consisting of any two of these values. Controlling the mass ratio of the lithium salt to the first additive within this range can provide film formation stability, reduce the risk of corrosion to the current collector, more effectively promote the insertion and extraction of lithium ions, promote the formation of a more stable SEI, reduce the occurrence of side reactions, and inhibit the metal dissolution of the positive electrode active material, thereby further improving the cycle performance of the secondary battery.
[0078] It should be noted that the present application does not specifically limit the method for preparing the electrolyte, and those skilled in the art can prepare it into an electrolyte according to conventional technical means, for example, by uniformly mixing an organic solvent, a lithium salt, and an additive.
[0079] An embodiment of the present application provides a secondary battery, comprising the electrolyte described above.
[0080] In one embodiment, the secondary battery further includes a positive electrode sheet and a negative electrode sheet.
[0081] More specifically, the positive electrode sheet includes a positive electrode current collector and a positive electrode active material layer disposed on at least one surface of the positive electrode current collector, wherein the positive electrode active material layer includes a positive electrode active material.
[0082] In one embodiment, the positive electrode active material can be selected from sodium iron composite oxide, sodium cobalt composite oxide, sodium manganese composite oxide, sodium nickel composite oxide, sodium nickel titanium composite oxide, sodium nickel manganese composite oxide, sodium iron manganese composite oxide, sodium nickel cobalt manganese composite oxide, sodium iron phosphate compound, sodium manganese phosphate compound, sodium cobalt phosphate compound, etc. However, the present application is not limited to these materials, and other traditional materials that can be used as negative electrode active materials for batteries can also be used. These positive electrode active materials can be used alone or in combination of two or more.
[0083] In one embodiment, the positive electrode active material includes at least one of lithium cobalt oxide, lithium iron phosphate, and a ternary composite material.
[0084] In one embodiment, the positive electrode material includes lithium iron phosphate.
[0085] In one embodiment, the positive electrode material includes a ternary composite material.
[0086] In one embodiment, the ternary composite material includes Li a Ni x Co y Mn z M b O d At least one of the compounds shown;
[0087] Among them, 0.9≤a≤1.1, 0<x<1, 0<y<1, 0<z<1, 0≤b≤0.1, 1≤d≤2; M includes at least one of Zr, W, Zn, Cu, Cr, Mg, Fe, V, Y, Nb, Ti, In, Ce, Sr, Sb, and B.
[0088] In the present application, the type of positive electrode current collector is not particularly limited, and it can be any known material suitable for use as a positive electrode current collector. In one embodiment, the positive electrode current collector includes metal materials such as aluminum, stainless steel, nickel plating, titanium, tantalum, and carbon materials such as carbon cloth and carbon paper.
[0089] There is no particular restriction on the form of the positive electrode current collector. When the positive electrode current collector is a metal material, the positive electrode current collector may be in the form of metal foil, metal cylinder, metal strip roll, metal plate, metal foil, metal plate mesh, stamped metal, foamed metal, etc. When the positive electrode current collector is a carbon material, the positive electrode current collector may include but is not limited to a carbon plate, a carbon film, a carbon cylinder, etc.
[0090] In one embodiment, the positive electrode active material layer further includes a conductive agent and a binder.
[0091] In one embodiment, the secondary battery further includes a negative electrode plate, wherein the negative electrode plate includes a negative electrode current collector and a negative electrode active material layer disposed on at least one surface of the negative electrode current collector, wherein the negative electrode active material layer includes a negative electrode active material.
[0092] In the present application, there is no particular limitation on the negative electrode current collector, as long as the purpose of the present application can be achieved, for example, it can be copper foil, copper alloy foil, nickel foil, stainless steel foil, titanium foil, foam nickel, foam copper or a composite current collector.
[0093] In one embodiment, the negative electrode active material can be natural graphite, artificial graphite, mesophase microcarbon beads (MCMB), hard carbon, soft carbon, silicon, silicon-carbon composite, SiO, Li-Sn alloy, Li-Sn-O alloy, Sn, SnO, SnO2, spinel structured lithium titanate Li4Ti5O 12 , at least one of Li-Al alloy and metallic lithium.
[0094] In one embodiment, the negative electrode active material layer further includes a conductive agent and a binder.
[0095] In one embodiment, the type of the conductive agent mentioned in the present application is not limited, and any known conductive agent can be used.
[0096] In one embodiment, the conductive agent includes at least one of carbon materials such as acetylene black, needle coke, carbon nanotubes, and graphene.
[0097] In one embodiment, the type of the binder mentioned in the present application is not limited, and any known positive electrode binder can be used.
[0098] In one embodiment, the binder includes at least one of polyethylene, polypropylene, polyethylene terephthalate, polymethyl methacrylate, polyimide, aromatic polyamide, cellulose, nitrocellulose, styrene-butadiene rubber, nitrile rubber, fluororubber, isoprene rubber, polybutadiene rubber, ethylene-propylene rubber, styrene-butadiene-styrene block copolymer or its hydrogenate, ethylene-propylene-diene terpolymer, styrene-ethylene-butadiene-ethylene copolymer, styrene-isoprene-styrene block copolymer, isotactic-1,2-polybutadiene, polyvinyl acetate, ethylene-vinyl acetate copolymer, propylene-α-olefin copolymer, polyvinylidene fluoride, polytetrafluoroethylene, fluorinated polyvinylidene fluoride, and polytetrafluoroethylene-ethylene copolymer.
[0099] In the secondary battery mentioned in the present application, a separator is usually provided between the positive electrode and the negative electrode to prevent short circuit. The material and shape of the separator are not particularly limited as long as the effect of the present application is not significantly impaired.
[0100] In one embodiment, the separator includes a porous sheet or non-woven fabric having excellent liquid retention. The materials of the resin or glass fiber separator include, but are not limited to, polyolefin, aromatic polyamide, polytetrafluoroethylene, polyethersulfone, and the like.
[0101] In one embodiment, the polyolefin is polyethylene or polypropylene. In some embodiments, the polyolefin is polypropylene. The materials of the above-mentioned diaphragm can be used alone or in any combination.
[0102] In some embodiments, the secondary battery may include an outer package, which may be used to encapsulate the electrode assembly and the electrolyte.
[0103] In some embodiments, the outer packaging of the secondary battery may be a hard shell, such as a hard plastic shell, an aluminum shell, a steel shell, etc. The outer packaging of the secondary battery may also be a soft package, such as a bag-type soft package. The material of the soft package may be plastic, and examples of the plastic include polypropylene, polybutylene terephthalate, and polybutylene succinate.
[0104] The present application has no particular limitation on the shape of the secondary battery, which may be cylindrical, square, or any other shape.
[0105] An embodiment of the present application provides an electric device, comprising the secondary battery described above, wherein the secondary battery serves as a power supply for the electric device.
[0106] Exemplarily, the above-mentioned electrical devices may include mobile devices (such as mobile phones, laptops, etc.), electric vehicles (such as pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.), electric trains, ships and satellites, energy storage systems, etc., but are not limited thereto.
[0107] The present application is further described below with specific embodiments:
[0108] Example 1
[0109] A method for preparing a secondary battery comprises the following steps:
[0110] (1) Preparation of electrolyte: At room temperature, in a glove box filled with argon (H2O < 1 ppm,
[0111] O2 <1ppm), mix EC and EMC in a mass ratio of 3:7, and use The molecular sieve is used to remove water to obtain a mixed solvent, and lithium salt A1 (the amount added is shown in Table 1) is added gradually to the obtained mixed solvent, and the mixture is stirred continuously and cooled with dry ice to ensure that the electrolyte temperature does not rise by more than 2°C, and finally a colorless transparent liquid is obtained, and then lithium difluorooxalatoborate (LiODFB) and vinyl sulfate (DTD) are added to obtain an electrolyte, wherein the mass percentage of lithium difluorooxalatoborate is 0.5%, and the mass percentage of vinyl sulfate is 1%;
[0112] (2) Preparation of positive electrode sheet: The positive electrode active material Li (Ni 0.8 Mn 0.1 Co 0.1 )O2(NMC811) is evenly mixed with conductive agent acetylene black (SuperP) and binder polyvinylidene fluoride (PVDF) in a mass ratio of 94:3:3, and evenly dispersed in 1-methyl-2-pyrrolidone (NMP) to form a uniform black slurry. The mixed black slurry is coated on both sides of the aluminum foil, and then baked, rolled and cut into pieces to obtain the positive electrode sheet.
[0113] (3) Preparation of negative electrode sheet
[0114] The negative electrode active material graphite, the conductive agent acetylene black (SuperP) and the binder SBR are mixed evenly in a mass ratio of graphite:SuperP:SBR=94:3:3, and evenly dispersed in deionized water to form a uniform black slurry. The mixed slurry is coated on both sides of the copper foil, and then baked, rolled and cut into pieces to obtain the negative electrode sheet.
[0115] (4) Production of secondary batteries
[0116] The prepared positive electrode sheet, separator, and negative electrode sheet are stacked in order, with the separator placed between the positive and negative electrode sheets. A bare battery cell is obtained by winding, hot pressing, and welding the tabs. The bare battery cell is placed in an outer packaging aluminum-plastic film and baked in an oven at 85±10°C for 24 hours. The prepared electrolyte is injected into the dried battery, allowed to stand, formed, and divided to complete the preparation of the secondary battery.
[0117] Embodiments 2 to 17
[0118] The difference between Examples 2 to 6 and Example 1 is that the amount of lithium salt A1 is adjusted.
[0119] The difference between Examples 7 to 13 and Example 1 is that the type of lithium salt is adjusted.
[0120] The difference between Examples 14 to 16 and Example 1 is that the amount of the additive is adjusted.
[0121] The difference between Example 17 and Example 1 is that the type of additive is adjusted.
[0122] The difference between Example 18 and Example 2 is that the positive electrode active material is replaced by LiFePO4.
[0123] Comparative Example 1
[0124] The difference between Comparative Example 1 and Example 1 is that no lithium salt is added in Comparative Example 1.
[0125] Comparative Example 2
[0126] The difference between Comparative Example 2 and Example 1 is that LiPF6 is used in Comparative Example 2 to replace lithium salt A1.
[0127] Performance Testing
[0128] 1. Room temperature DCR test: At 25±2℃, the soft pack batteries obtained from each implementation case and comparative example are charged to 4.2V at 1C, then discharged at 1C capacity for 30min, adjusted to 50% SOC, and then discharged at 10C constant current pulse for 10s. Then, the SOC is adjusted to 50% according to the above SOC adjustment method, and then charged for 10s. The DCR is calculated as (voltage before pulse discharge-voltage after pulse discharge) / discharge current*100%. After 500 cycles, the DCR is tested again, and the DCR change rate=(DCR of 500 cycles-initial DCR) / initial DCR*100%. The recorded results are shown in Table 1.
[0129] 2. Normal temperature cycle performance test: At 25±2°C, the soft-pack batteries obtained from each implementation case and comparative example were subjected to charge and discharge cycle tests at a charge and discharge rate of 4C / 1C in the range of 2.8 to 4.2V, and the battery's first-week discharge capacity and the discharge capacity after 500 cycles were recorded. The capacity retention rate of 500 weeks = 500-week discharge capacity / first-week discharge capacity*100%, and the recorded data are shown in Table 1.
[0130] 3. High temperature storage performance: The soft pack batteries obtained from each implementation case and comparative example were placed at 60±2°C, and the charge and discharge test was performed at a charge and discharge rate of 1C / 1C in the range of 2.8 to 4.2V, and the first week discharge capacity of the battery was recorded. After that, the battery was stored at 60±2°C for 30 days, and the charge and discharge test was performed again and the discharge capacity was recorded. High temperature storage capacity retention rate = discharge capacity after 7 days / first week discharge capacity*100%, and the recorded data is shown in Table 1.
[0131] 4. Lithium precipitation test: adjust the temperature to -10℃, charge to 4.2V with 0.23C charging current, discharge to 2.8V with 1C discharging current, cycle 10 times, adjust the temperature to 25℃, charge to 4.2V with 1C charging current, disassemble and observe the interface.
[0132] Table 1 Electrolyte parameters
[0133]
[0134] Table 2 Performance test table
[0135]
[0136]
[0137] It can be seen from Table 2 that the electrolyte containing the lithium salt described in the present application can significantly improve the fast charging performance and cycle performance, and effectively reduce the DCR.
[0138] It can be seen from the comparison of Examples 1 to 6 that by controlling the mass percentage of the lithium salt in the electrolyte to 8 to 20%, the fast charging performance and the cycle performance are further improved, and the DCR is further reduced.
[0139] By comparing Examples 1 to 4 with Examples 14 to 17, it can be seen that by controlling the mass ratio of lithium salt to additive to (5 to 14): 1, the fast charging performance and cycle performance are further improved, and the DCR is further reduced.
[0140] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present application rather than to limit the scope of protection of the present application. Although the present application has been described in detail with reference to the preferred embodiments, ordinary technicians in this field should understand that the technical solution of the present application can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present application.
Claims
1. An electrolyte, characterized in that: Including a lithium salt, the lithium salt includes at least one of the compound shown in formula I and the compound shown in formula II: In Formula I, R1 comprises at least one of C1-C6 alkylene and C1-C6 alkylene ether; R2 comprises C3-C 20 Alkyl ethers; In formula II, R3 comprises at least one of C1-C6 alkylene and C1-C6 alkylene ether; R4 comprises C3-C 20 Alkyl ether.
2. The electrolyte according to claim 1, characterized in that The R1 comprises at least one of C1-C2 alkylene and C1-C2 alkylene ether; R2 comprises C3-C6 alkyl ether; and / or The R3 includes at least one of C1-C2 alkylene and C1-C2 alkylene ether; and R4 includes C3-C6 alkyl ether.
3. The electrolyte according to claim 1, characterized in that Satisfy at least one of the following (a) to (b): (a) The compound represented by formula I comprises at least one of the following compounds: (b) The compound represented by formula II comprises at least one of the following compounds:
4. The electrolyte according to claim 1, characterized in that The mass percentage of the lithium salt in the electrolyte is 8-20%.
5. The electrolyte according to claim 1, characterized in that The electrolyte further includes a first additive, which includes at least one of a sulfur-containing additive and a boron-containing additive; the mass percentage of the first additive in the electrolyte is 0.1-6%.
6. The electrolyte according to claim 5, characterized in that The sulfur-containing additive includes at least one of 1,3-propane sultone, vinyl sulfate, and methylene methane disulfonate; and / or The boron-containing additive is at least one of lithium difluorooxalate borate, lithium dioxalate borate and lithium tetrafluoroborate.
7. The electrolyte according to claim 5, characterized in that The first additive includes a sulfur-containing additive and a boron-containing additive. The mass percentage of the sulfur-containing additive in the electrolyte is 0.1-3%; the mass percentage of the boron-containing additive in the electrolyte is 0.1-3%.
8. The electrolyte according to claim 1, characterized in that In the electrolyte, the mass ratio of the lithium salt to the first additive is (5-14):
1.
9. A secondary battery, characterized in that: The electrolyte comprises the electrolyte described in any one of claims 1 to 8.
10. An electrical device, characterized in that: The secondary battery according to claim 9 is included, and the secondary battery is used as a power supply for the electrical device.
Citation Information
Cited By
High-temperature electrolyte for lithium ion battery and lithium ion battery
CN121331952A